Factors influencing the social media usage among entrepreneur of food and beverage during Covid-19 pandemic - Nur Amanina, Mohamad Bakri (2021)
The internet and mobile technologies have changed our daily lives, not only in terms of consumption but also in terms of business. Social media also has been recognized as one of the online platforms for business that makes the entrepreneur can getting benefit from it in competition with large corporations. This study aims to investigate factors influencing the social media usage among entrepreneurs of food and beverage during the COVID-19 pandemic by using the technology acceptance model, the Unified Theory of Acceptance and Use of Technology (UTAUT). The relational analysis is used in this study, which is a quantitative study that operates between variables. The data of 200 respondents were collected via google forms in the Kedah area to testing the proposed model with empirical data. The result of the study concludes that performance expectancy, effort expectancy, and social influence have a strong relationship with behavior intention in using social media as business tools. In addition, facilitating conditions moderately influence user behavior while behavior intention have directly significant relationship towards the usage behavior of social media among entrepreneurs of food and beverage during the COVID-19 pandemic.